Människors inställning till fiskvälfärd - Eriksson, Maria (SLU/Dept. of Animal Environment and Health (until 231231), 2022)
Animal welfare is a question of increasing importance for consumers around the world. Consumers’ attitudes toward animals are important drivers when it comes to safeguarding factors in the welfare of farm animals. Fish is an animal that man benefits from in several ways. Yet fishes are seldom given any moral regard; they are counted in tonnes instead of individuals and are largely neglected in both animal welfare legislation and hunting legislation worldwide. This study analysed Swedish consumers’ attitudes towards an improved animal welfare and legislation for both wild and farmed fish. A survey was conducted using the program Netigate. During a period of two weeks during 2022, a total of 227 survey answers were collected. Most of the participants thought that animal welfare was important for both wild and farmed fish. They also thought that it was important that both stress and suffering is minimized during their slaughter process. Most participants did not know how farmed fish in Sweden usually are stunned during slaughter. The participants thought that animal welfare legislation was more important for farmed fish than wild. A difference in attitude was seen between men and women, where women had a stronger perception that fish can suffer, feel pain and are intelligent animals. On average, women felt stronger about the importance of animal welfare legislation for farmed and wild fish, and that it is equally important that farmed and wild fish are treated well. A difference in attitudes was also seen between different age groups. The perceptions that fish can suffer and feel pain, that fish are intelligent animals and that it is equally important that farmed and wild fish are treated well decreased as the age of the respondents increased. A difference in respondents’ attitudes was also seen between those who had education related to animals or animal husbandry and those who did not. Those who had some education in the animal field had a stronger perception that fish can suffer, feel pain and that fish are intelligent animals. Those who had animal education also had a stronger perception about the importance of animal welfare legislation for farmed and wild fish. Differences in the animal welfare legislation was seen between wild and farmed fish where legislation for wild fish was seen to be largely neglected compared to the current legislation for farmed fish. At the same time current legislation for farmed fish was found to be inadequate as no species-specific guidelines are available. This study showed that consumer attitudes are starting to change, which may influence fish welfare and our communities in the near future.